2013
DOI: 10.1107/s1744309113017004
|View full text |Cite
|
Sign up to set email alerts
|

Protein preparation, crystallization and preliminary X-ray analysis ofPolygonum cuspidatumbifunctional chalcone synthase/benzalacetone synthase

Abstract: The chalcone synthase (CHS) superfamily of type III polyketide synthases (PKSs) generate the backbones of a variety of plant secondary metabolites. An active bifunctional chalcone synthase/benzalacetone synthase (CHS/BAS) from Polygonum cuspidatum was overexpressed in Escherichia coli as a C-terminally polyhistidine-tagged fusion protein, purified to homogeneity and crystallized using polyethylene glycol 4000 as a precipitant. The production of well shaped crystals of the complex between PcPKS1 and benzalaceto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…There are many PKS super family genes, known as CHS-like genes, including genes encoding stilbene synthase (STS), 2-pyrone synthase (2-PS), benzalacetone synthase, biphenyl synthase, phlorisovalerophenone synthase, p-coumaroyltriacetic acid synthase, aloesone synthase, hexaketide synthase, pentaketide chromone synthase, etc. [21][22][23][24][25][26][27]. CHS-like genes differ from CHS in many aspects, such as their initial substrates, intermediate products and catalytic mechanisms, etc.…”
Section: Introductionmentioning
confidence: 99%
“…There are many PKS super family genes, known as CHS-like genes, including genes encoding stilbene synthase (STS), 2-pyrone synthase (2-PS), benzalacetone synthase, biphenyl synthase, phlorisovalerophenone synthase, p-coumaroyltriacetic acid synthase, aloesone synthase, hexaketide synthase, pentaketide chromone synthase, etc. [21][22][23][24][25][26][27]. CHS-like genes differ from CHS in many aspects, such as their initial substrates, intermediate products and catalytic mechanisms, etc.…”
Section: Introductionmentioning
confidence: 99%
“…CHS is a representative of the CHS family. This family also includes other members such as biphenyl synthase [ 5 ], 2-pyrone synthase (2-PS) [ 6 ], benzalacetone synthase [ 7 ], stilbene synthase [ 8 ], bibenzyl synthase [ 9 ], benzophenone synthase [ 10 ], pentaketide chromone synthase [ 11 ], octaketide synthase [ 12 ] and p -coumaroyltriacetic acid synthase [ 13 ]. All these other enzymes have differences from CHS in many aspects, such as the choice of initial substrates, the number of condensation reactions, and the mechanisms by which the resulting intermediates are cyclized and aromatized.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of PcPKS1 from Polygonum cuspidatum (Japanese knotweed) was also recently solved, and studies showed PcPKS1 to have both CHS and BAS activities [47]. Unlike rhubarb BAS and the classical BAS PcPKS2, the 'gatekeeper' Phe215 remained in PcPKS1, thus suggesting a different catalytic mechanism in the bifunctional PcPKS1.…”
Section: Benzalacetone Synthasementioning
confidence: 99%